Seco-4-methyl-DCK derivatives as potent chemosensitizers. Issue 1 (1st January 2019) - Guo, Yalan; Wang, Ke; Chen, Xiaoyu; Li, Haihong; Wan, Qi; Morris-Natschke, Susan; Lee, Kuo-Hsiung; Chen, Ying
Graphical abstract: Highlights: Opening C-ring to synthesize a series simplified DCK analogs. Displaying significant MDR reversal activities in the P-gp overexpressing cancer cell lines. Undetected reversal activity in a non-P-gp overexpressing cisplatin resistant human ovarian cancer cell lines. Showing more than 496 and 735 reversal ratios at 10 μM concentration of compounds7o and7y . Hardly having significant cytotoxicity to the tested cell lines. Abstract: Twenty-five seco-4-methyl-DCK derivatives were designed, synthesized and evaluated for chemoreversal activity when combined with paclitaxel or vincristine in two drug-resistant cancer cell lines (A2780/T and KB-V) respectively. Most of the new compounds displayed moderate to significant MDR reversal activities in the P-gp overexpressing A2780/T and KB-V cells. Especially, compounds7o and7y showed the most potent chemosensitization activities with more than 496 and 735 reversal ratios at a concentration of 10 μM. Unexpectedly the newly synthesized compounds did not show chemosensitization activities observed in a non-P-gp overexpressing cisplatin resistant human ovarian cancer cell line (A2780/CDDP), implying that the MDR reversal effects might be associated with P-gp overexpression. Moreover, these compounds did not exhibit significant antiproliferative activities against nontumorigenic cell lines (HUVEC, HOSEC and T29) compared to the positive control verapamil at the tested concentration, which suggested better safety than verapamil. The pharmacological actions of the compounds will be studied further to explore their merit for development as novel candidates to overcome P-gp mediated MDR cancer.